Komponen Pengembangan Kurikulum - Setiyadi, Bradley; Rohima, Rohima; Sari, Yulia; Yani, Mince Andri (Jurnal Likhitaprajna, 2020)
Curriculum is the core of education which is simply a curriculum that can be interpreted as something that is taught while learning is a tool to teach material. While the meaning of learning is more an effort to implement the strategy method of how the teaching takes place so that students can understand learning and then the approach between those who teach and those taught so that the knowledge taught or the material taught can be conveyed properly. Learning is also an implementation of the curriculum both in the classroom and outside hard and so on. Not only to the extent that the curriculum must also have good components so that the goals of education can be achieved so that various components are achieved. The curriculum is also seen as a subsystem of education both in general and specifically that reveals the hierarchy and interrelationships of various components that contain the objectives of education, the content of education, how educational methods are taught and finally how to evaluate when learning can be carried out with whether or not implemented with the established curriculum guidelines. This paper uses a method in the form of a theoretical study of the components of curriculum development. The theories put forward in this paper are theories about the curriculum and its developers, plus theories about curriculum development approaches, learning and evaluation of curriculum development.